MANAJEMEN KONFLIK DALAM ORGANISASI PENDIDIKAN PERSPKETIF STEPHEN P. ROBBINS - Aftori, Rahmatika; Saguni, Fatimah; Ruslin (ISTIQRA: Jurnal Hasil Penelitian, 2021)
This study examines the dynamics of conflict management in educational institutions with the aim of photographing the phenomenon of functional and dysfunctional conflict in educational organizations. With a library research design by Stephen P. Robbins, this research uses a qualitative descriptive approach through content analysis. The results of this study show that the interactionist view divides conflict into two types, namely functional and dysfunctional conflicts. For conflict management techniques,principals can apply several techniques in managing conflict in schools, including: problem solving, superior goals, resource expansion, anticipation, pressing, compromise, authoritative command, changing human variables and structural variables.